Analysis of Student Errors in Solving Word Problems using Polya Steps - Vanesa Aftina; Susi Herawati; Listy Vermana (Pendidikan Matematika UNIMOR, 2024)
This research was motivated by the many difficulties experienced by students in the mathematics learning process which had an impact on the occurrence of errors in working on mathematics story problems. These errors need to be known so that it is easier to find solutions so that these errors can be minimized. This research aims to determine the types and causes of errors made by students in solving mathematics story problems on single interest and compound interest materials using Polya's steps. This research method is qualitative with descriptive research type. The research subjects consisted of 2 students from 13 class XI TKP SMKN 1 Pariaman students, with the criteria being 1 student each from the medium group and 1 student from the low group. Data collection techniques include tests and interviews. The results of the research show that the percentage of errors made by students in solving mathematics story problems on single interest and compound interest material using Polya steps is: in question number 1, the biggest error made in the step of understanding the problem was 23.08%. Question number 2, the biggest error made during the rechecking step was 15.38%. In question number 3, the biggest mistake made in the step of understanding the problem was 19.23%. The factors that cause students to make mistakes include, not being used to writing information on questions using their own words, not writing down what they know and what is asked in the question correctly, not focusing when working on questions, not being careful in carrying out the calculation process, not being used to checking again, and rushing through the settlement process.